2019
DOI: 10.7150/thno.29698
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Sox2 are required for Melanoma Tumor-Repopulating Cell Dormancy

Abstract: Tumorigenic cells, when facing a hostile environment, may enter a dormant state, leading to long-term tumor survival, relapse, and metastasis. To date, the molecular mechanism of tumor cell dormancy remains poorly understood. Methods: A soft, 3-dimentional (3D) fibrin gel culture system was used to mechanically select and grow highly malignant and tumorigenic melanoma tumor-repopulating cells (TRCs). We cultured control melanoma TRCs, TRCs with Sox2 knockdown, TRCs with Sox2 knockout, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…For instance, SOX2 has been shown to contribute to melanoma metastasis 35 and to be highly expressed in melanomas compared to nevi 36 . In addition, SOX2 regulates survival, self-renewal, and tumorigenicity of human melanoma-initiating cells 11 , 37 and participates in dormancy regulation of melanoma tumor-repopulating cells 38 . SOX2 has been recently related to the acquisition of an aggressive oxidative tumor phenotype endowed with enhanced drug resistance and metastatic ability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SOX2 has been shown to contribute to melanoma metastasis 35 and to be highly expressed in melanomas compared to nevi 36 . In addition, SOX2 regulates survival, self-renewal, and tumorigenicity of human melanoma-initiating cells 11 , 37 and participates in dormancy regulation of melanoma tumor-repopulating cells 38 . SOX2 has been recently related to the acquisition of an aggressive oxidative tumor phenotype endowed with enhanced drug resistance and metastatic ability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this may be the main reasons for the inconsistency between PD-1 knockout and knockout. Although knockdown and knockout are often used to verify each other, the results observed by these two methods sometimes still lead to inconsistent conclusions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor dormancy is an important process implicated in tumor immune escape and drug resistance (128,129). Jia et al showed that low levels of SOX2 expression are linked to cycle arrest, melanoma cell stemness and tumor dormancy leading long-term tumor survival, and relapse (130).…”
Section: Melanoma Microenvironment Acidification and Its Influence Onmentioning
confidence: 99%